Atrial fibrillation activation patterns predict freedom from arrhythmias after catheter ablation: utility of ExTRa mapping™ - Aoyama, Daisetsu; Miyazaki, Shinsuke; Hasegawa, Kanae; Nomura, Ryohei; Kakehashi, Shota; Mukai, Moe; Miyoshi, Machiko; Yamaguchi, Junya; Sato, Yusuke; Shiomi, Yuichiro; Ikeda, Hiroyuki; Ishida, Kentaro; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Mechanisms underlying atrial fibrillation (AF) are widely complex and vary tremendously among individuals.Objectives: This retrospective study aimed to investigate the association between AF activation patterns and clinical outcomes post-ablation.Methods: Fifty-five AF patients (64.012.9 years; 41 men; 17 paroxysmal) underwent bi-atrial endocardial driver mapping during AF pre-ablation with a real-time phase mapping system (ExTRa Mapping). The nonpassively activated ratio (%NP) of meandering rotors and multiple wavelets relative to the recording time was evaluated in 26 atrial segments (15 in the left atrium [LA] and 11 in the right atrium). Irrespective of the mapping results, all patients underwent standard AF ablation via cryoballoons and/or radiofrequency catheters.In a median follow-up interval of 27(14-30) months, 69.1% of patients were free from recurrent arrhythmias and antiarrhythmic drugs at one year post-procedure. Patients with recurrent AF were more likely to have non-paroxysmal AF, a significantly larger LA size, and higher LA maximal %NP(LAmax%NP) and LA anterior wall %NP(LAAW%NP) than those without recurrent AF. A multivariate Cox regression analysis showed that both an LAmax%NP (hazard ratio [HR]=1.075; 95% confidence interval [CI]=1.02-1.14, p=0.012) and LAAW%NP (HR=1.061; 95% CI=1.01-1.11, p=0.013) were independent predictors of atrial arrhythmia recurrence. The optimal cutoff points for the LAmax%NP and LAAW%NP for predicting AF recurrence were 64.5% and 60.0%, respectively. A Kaplan−Meier analysis demonstrated that both an LAmax%NP>64.5% (p=0.0062) and LAAW%NP>60.0% (p=0.014) were associated with more frequent AF recurrences.Baseline AF activation pattern mapping may aid in predicting freedom from arrhythmias after standard AF ablation procedures.